The Impact of the SEHATI Program on Interest in Applying for Halal Certification for MSMEs - Ardiansyah Ihsan (ADL ISLAMIC ECONOMIC : Jurnal Kajian Ekonomi Islam, 2025)
This study aims to analyze the effect of the Free Halal Certification Program (SEHATI) on the interest of MSMEs in applying for halal certification at the Ministry of Religious Affairs in Prabumulih City. The research design uses a quantitative approach with a Likert scale questionnaire for 80 MSME respondents. Primary and secondary data were analyzed through instrument testing, simple linear regression, and hypothesis testing (t-test). The results show that SEHATI has a positive and significant effect on the interest of MSMEs in registering for halal certification (t-count = 2.673; p < 0.05). The regression model explains 71.9% of the variation in interest (R² = 0.719), while 28.1% is influenced by other variables outside the model. These findings indicate that intensifying the program (through socialization, administrative assistance, and technical guidance) has the potential to increase the intention of MSMEs to apply for certification. The practical implications for program managers are to strengthen one-stop services, simplify requirements, and expand the scope of guidance so that the impact of the program is more evenly distributed.